Succinate in innate immunity: linking metabolic reprogramming to immune modulation - Atallah, Reham; Gindlhuber, Juergen; Heinemann, Akos (Frontiers in Immunology, 2025)
Succinate is an essential metabolite in the tricarboxylic acid (TCA) cycle. In mitochondria, succinate holds a unique position connecting the TCA cycle and the electron transport chain (ETC), thereby providing a shortcut path for adenosine triphosphate (ATP) production. Beyond this fundamental role in cellular metabolism, succinate is increasingly acknowledged as a key modulator of immune cell function. Production of reactive oxygen species (ROS), hypoxia-inducible factor-1α (HIF-1α) stabilization, protein succinylation and cell-cell communication mediated by succinate receptor 1 (SUCNR1) are traits induced by succinate. During inflammation, succinate plays key dual roles, culminating in either pro- or anti-inflammatory effects that are tissue- and context-dependent. In this review, we provide a succinct overview focusing on the regulatory role of succinate in innate immune cells, highlighting involved mechanisms and research gaps that represent promising targets for future study.